Growth of Cu-Zn5 and Cu5Zn8 intermetallic compounds in the Sn-9Zn/Cu joint during liquid state aging - Ramani, Mayappan (Universiti Malaysia Perlis, 2010)
International Conference on X-Rays and Related Techniques in Research and Industry (ICXRI 2010) jointly organized by Universiti Malaysia Perlis (UniMAP) and X-Ray Application Malaysia Society (XAPP), 9th - 10th June 2010 at Aseania Resort Langkawi, Malaysia.